Linguistic Landscape Analysis of Language Function at Tourist Places Signboard in Banjar Bali - Dewi, Kadek Linda Puspita; Putra, I Nyoman Adi Jaya; Paramarta, I Made Suta (STKIP Agama Hindu Singaraja, 2024)
This research aims to identify signboards at three tourist places in Banjar District, namely Brahmavihara Arama Banjar, Air Panas Banjar and Krisna Funtastic Land in terms of the function of the language on the signboards and the languages used on the signboard. This research was designed using qualitative descriptive research and data collection was carried out using observation and documentation techniques from signboards at three tourist attractions in Banjar District, namely Brahmavihara Arama, Banjar Hot Springs, and Krisna Funtastic Land. The function of language on public space signs in three tourist attractions in Banjar District (Brahmavihara Arama, Banjar Hot Springs and Krisna Funtastic Land) was found to be informational, symbolic, mythological and commercial. These four functions were analyzed based on the theory from Yanhong and Rungruang (2013) regarding the function of language on public space signs. The result of this research found that information functions, commercial functions and mythological functions are found on public signs at the three tourist places, namely Brahmavihara Arama Banjar, Banjar Hot Springs and Krisna Funtastic Land. Meanwhile, symbolic functions are only found in two tourist attractions, namely Krisna Funtastic Land and Brahmavihara Arama Banjar. And the language used on the public space signs at these three tourist places uses more than one language or is called bilingual public space signage.